Multiscale Geometric Design Principles Applied to 3D Printed Schwarzites. Issue 1 (15th November 2017) - Sajadi, Seyed Mohammad; Owuor, Peter Samora; Schara, Steven; Woellner, Cristiano F.; Rodrigues, Varlei; Vajtai, Robert; Lou, Jun; Galvão, Douglas S.; Tiwary, Chandra Sekhar; Ajayan, Pulickel M.
Abstract: Schwartzites are 3D porous solids with periodic minimal surfaces having negative Gaussian curvatures and can possess unusual mechanical and electronic properties. The mechanical behavior of primitive and gyroid schwartzite structures across different length scales is investigated after these geometries are 3D printed at centimeter length scales based on molecular models. Molecular dynamics and finite elements simulations are used to gain further understanding on responses of these complex solids under compressive loads and kinetic impact experiments. The results show that these structures hold great promise as high load bearing and impact‐resistant materials due to a unique layered deformation mechanism that emerges in these architectures during loading. Easily scalable techniques such as 3D printing can be used for exploring mechanical behavior of various predicted complex geometrical shapes to build innovative engineered materials with tunable properties. Abstract : Schwartzites are 3D porous solids with periodic minimal surfaces having negative Gaussian curvatures and can possess unusual mechanical and electronic properties. This work investigates their mechanical behavior, on the primitive and gyroid families across different length scales, after these geometries are 3D printed at centimeter length scales based on molecular models.